2019
DOI: 10.1002/mrd.23276
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation and supra‐zero temperature storage of cat germinal vesicles lead to less structural damage and similar epigenetic alterations compared to cryopreservation

Abstract: Understanding cellular and molecular damages in oocytes during exposure to extreme conditions is essential to optimize long‐term fertility preservation approaches. Using the domestic cat (Felis catus) model, we are developing drying techniques for oocytes’ germinal vesicles (GVs) as a more economical alternative to cryopreservation. The objective of the study was to characterize the influence of desiccation on nuclear envelope conformation, chromatin configuration, and the relative fluorescent intensities of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
3
8
0
Order By: Relevance
“…Our recent study on oocytes' germinal vesicles in domestic cat showed similar effect of vitrification and dehydration protocols on epigenetic patterns but indicated less structural damage after dehydration and rehydration compared to vitrification and warming [22]. Opposite to that, in our current study, ovarian tissue response to dehydration/rehydration seems to be more intense and potentially damaging to cells compared to vitrification/ warming.…”
Section: Vitrification Vs Dehydration Stresssupporting
confidence: 50%
See 1 more Smart Citation
“…Our recent study on oocytes' germinal vesicles in domestic cat showed similar effect of vitrification and dehydration protocols on epigenetic patterns but indicated less structural damage after dehydration and rehydration compared to vitrification and warming [22]. Opposite to that, in our current study, ovarian tissue response to dehydration/rehydration seems to be more intense and potentially damaging to cells compared to vitrification/ warming.…”
Section: Vitrification Vs Dehydration Stresssupporting
confidence: 50%
“…Our vitrification protocol has been optimized so there is no significant differences in percentage of morphologically normal follicles between vitrified/warmed and fresh cortical tissue, and only mild decrease in follicular viability and RNA synthesis [ 8 , 20 ]. Our laboratory also reported initial steps in the development of microwave-assisted dehydration technique for cat germinal vesicle [ 21 , 22 ], sperm cells [ 23 ], and most recently ovarian tissue [ 18 ], relying on intracellular delivery of trehalose as protection from dehydration/rehydration damage. After cortical tissue dehydration for up to 30 min followed by immediate rehydration, there was no significant change in the percentage of morphologically normal follicles or stromal cell density, and no significant increase in DNA damage; however, there was a significant decrease in RNA synthesis in follicles already after 10 min of drying [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global DNA methylation (5‐methylcytosine) level appears not to be affected by lyophilization in rabbit sperm (Mercati et al, 2020). The proportion of cat germinal vesicles with tri‐methylation of histone H3K4me3 (detected by immunostaining) after microwave drying is lower as observed during cryopreservation (P. C. Lee & Comizzoli, 2019). While partial microwave drying of cat testicular tissues showed that histomorphometry (>80%) and viability (>50%) of seminiferous tubules can be preserved (Silva et al, 2020), no epigenetic or transcriptional data are reported yet.…”
Section: Damages and Stresses On Biological Structures And Functions ...mentioning
confidence: 94%
“…Similarly, percentages of cat oocytes' nuclei (germinal vesicles) with intact DNA (comet assay) after air drying are lower (Graves‐Herring et al, 2013), but not as much as what cryopreservation triggers. Regarding nuclear envelopes and chromatin configuration, structural damages are not extensive in microwave‐dried germinal vesicles compared to cryopreservation in the domestic cat (P. C. Lee & Comizzoli, 2019). DNA integrity (via TUNEL assay) after partial microwave‐assisted dehydration has also been reported in ovarian and testicular tissues, in which about 50% of cells had intact DNA (P.‐C.…”
Section: Damages and Stresses On Biological Structures And Functions ...mentioning
confidence: 99%
“…Our aim in the current study was to validate and further characterize candidate proteins that can serve as markers of competent oocytes. Identification of these markers could help expand our understanding of oocyte development and be applied to improve ART by using them to assess the efficacy of female fertility preservation methods, especially ones focusing on preservation of the GV alone ( Graves-Herring et al, 2013 ; Elliott et al, 2015 ; Lee and Comizzoli, 2019 ).…”
Section: Introductionmentioning
confidence: 99%